Women and the politics of resistance in the Iranian constitutional revolution - Dezhamkhooy, Maryam (Palgrave pivot, 2023)
Most scholarship on the nineteenth and early twentieth century Constitutional Revolution in Iran has focused on the role of two groups, intellectuals and the clergy. The role of women has largely been ignored, despite their widespread participation in the Revolution, and existing research on women has mainly focused on their achievements in the realm of women’s rights, which means that other aspects of women’s activism remain un-investigated. The aim of this book is twofold: first, it presents one of the very first studies of women’s resistance strategies and their resistance to consumerism in Iran; second, and in relation to the first objective, it attempts to demonstrate the biased nature of knowledge production in the studies of women in past societies, particularly the role of women in economics. This book therefore explores the public role of women and their efforts to revive Iran’s economy during and after the Constitutional Revolution. Maryam Dezhamkhooy is an Affiliated Researcher at Heidelberg University, Germany